Internet of Things-Based Intelligent Health Monitoring System - Wardani, Sumita (Al'Adzkiya, 2022)
IoT in health monitoring is the main key in providing better medical facilities to patients and facilitating doctors and hospitals as well. The system proposed here consists of various medical devices such as sensors and web-based or mobile-based applications that communicate via a network of connected devices and help monitor and record health data and medical information. The proposed result of this mini research is to build a system to provide a medical monitoring system to patients even in remote areas without a hospital in their area by connecting via the internet and retrieving information via their health status through the wearable device provided in the kit using raspberry pi microcontroller which can record patient's heart rate, blood pressure. The system will provide information to the patient's family members and doctors about the patient's current health status and this system has complete medical information in case of an emergency. Information retrieval can be used to analyze and predict chronic disorders or other diseases such as heart attack at its initial stage using data mining techniques which will also provide a profitable approach to decision making.